2022
DOI: 10.1021/acsomega.2c02557
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Heat Transfer Correlation for Micro/Nanostructure Properties of Surfaces

Abstract: Condensation, which can be observed in nature as a phase change heat transfer phenomenon, is a critical phenomenon in industrial fields such as power generation, water desalination, and environmental control. Many existing studies have applied surfaces with different wettability by controlling the surface topology to enhance condensation heat transfer. However, the industrial applicability is close to zero due to the limited size and shape of surfaces and low supersaturation conditions. Here, we regulate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For a Reynolds number of 10,000, the saturation pressure was increased incrementally from 0.2 bar to 0.6 bar, assigning Conditions 1 through 3 for each 0.2 bar interval. Once the saturation pressure reached 0.6 bar, the supersaturation level was elevated by adjusting the Reynolds number to 20,000 (Condition 4), followed by a decrease in saturation pressure to 0.4 bar (Condition 5) [29].…”
Section: Experimental Conditions For Condensing Performance Evaluationmentioning
confidence: 99%
“…For a Reynolds number of 10,000, the saturation pressure was increased incrementally from 0.2 bar to 0.6 bar, assigning Conditions 1 through 3 for each 0.2 bar interval. Once the saturation pressure reached 0.6 bar, the supersaturation level was elevated by adjusting the Reynolds number to 20,000 (Condition 4), followed by a decrease in saturation pressure to 0.4 bar (Condition 5) [29].…”
Section: Experimental Conditions For Condensing Performance Evaluationmentioning
confidence: 99%
“…In recent decades, people have become more and more familiar with micro-nano structural materials. It is found that micro-and nanomaterials have excellent hydrophobicity [68,69], high thermal conductivity [70], self-healing characteristics [71], biodegradability and compatibility [72,73], and have been applied to fields such as chemical coatings [74,75], biomedical devices [76,77], food safety [78,79], and photoelectric device manufacturing [80][81][82]. The combination of wood superhydrophobic coating and micronano particles effectively links the latest technology of micro-nano structure and green materials, with wide space for development.…”
Section: Introductionmentioning
confidence: 99%